Areas susceptible to lionfish invasion in the Mexican Pacific - Reyes-Bonilla, Héctor (2020)
Lionfish Pterois volitans/miles has invaded the western Atlantic, but is absent in the eastern tropical Pacific, even though the oceanographic conditions seem to be adequate for its establishment. This paper proposes probable Pterois spp invasion areas on the western coast of Mexico, based on ecological niche and potential distribution models, as well as species occurrence data (1985-2018) and environmental layers (2002-2017). For the environmental database, rasters of temperature, salinity, chlorophyll a and velocity of sea currents were used at average, maximum, and minimum values at the surface level, as well as average temperature and salinity at the seabed level and the type of predominant coast. Results indicated that bottom salinity, type of coast, and average surface temperature contributed 65% to the distribution model. To learn the impact of the possible invasion of Pterois spp. on local biodiversity, a spatial intersection was made between the predicted area with potential for invasion with the geographic distribution of coastal fish and the fishing areas. According to the spatial analysis, the arrival of Pterois spp. could affect almost 200 species, several of which are endemic and of commercial importance. The impact could be even greater, considering that the species is a predator of invertebrates such as crayfish and shrimp, which are important fisheries in the region.